Age Related Decline in Cortical Multifocal Flash VEP: Latency Increases Shown to Be Predominately Magnocellular - Brown, Alyse; Corner, Molly; Crewther, David; Crewther, Sheila (Frontiers in Aging Neuroscience, 2019)
Previous research has shown that as the visual system ages, flicker sensitivity decreases and visual evoked potential (VEP) latencies increase. To date, the extent to which these effects reflect age-related changes in the magnocellular (M) and parvocellular (P) pathways remains unclear. The aim of this study was to apply non-linear analysis of multifocal (mf)VEP to investigate changes in M and P driven cortical responses with age. We hypothesised that age would be associated with a lengthening of early latency response components and a decrease in temporal efficiency (amplitude ratio of first to second order) for M pathway components. In a sample of 86 participants with normal or corrected to normal vision, ranging in age from 18 to 78, we recorded mfVEP and flicker fusion thresholds for both low and high contrast stimuli. Ten participants were removed from the data set due to noisy recordings. As expected, a decrease in flicker fusion was seen with age, while M temporal efficiency was not strongly age-related. Nonlinear mfVEP recordings revealed that latencies of the N70 (K2.1) and N110 (K2.2) second order peaks increased with age suggesting that aging is associated with both M and P pathways. The steepest increases in latency were associated with the M dominated K2.1 (second order first slice) N70 components recorded at low and high contrast (11.7ms/decade and 10.4ms/decade, respectively). Interestingly, significant latency shifts were not observed in the first order responses. Significant decreases in amplitude were found in multiple first and second order components up to 30 years, after which amplitudes remained relatively constant. In conclusion, response latencies with M generated peaks were more susceptible to age than were P, though little evidence was found to support an impairment in neural efficiency with age.